وجوه الإعجاز في الخطاب الأسلوبي والمعرفي للقرآن الكريم (Wujuh al-i'jaz fi al-khitab al-uslubi wa al-ma'rifi lil-Qur'an al-Karim) = The Miraculous Aspects in the Stylistic & Epistemic Discourse in the Holy Qur´ān - Hussein, Nasr El Din Ibrahim Ahmed (IIUM Press, 2002)
The Miraculous Aspects in the Stylistic & Epistemic Discourse in the Holy Qur´ān